Databook of solvents - Wypych, Anna; Wypych, George (ChemTec Publishing, 2019)
Databook of Solvents, Second Edition, has been redesigned to include all high production volume solvents and has been completely updated with the most up-to-date findings, data and commercial developments. With more than 250 of the most essential solvents used in everyday industrial practice, the book includes their physical properties, health and safety considerations (such as carcinogenicity, reproduction/developmental toxicity, flammability), and first aid guidance. Emphasis is placed on cost-saving and efficient replacements for more toxic solvents. Detailed information is also given for usage considerations, including outstanding properties, potential substitutes, features, and recommended benefits for each solvent.